Effect of Traditional and Commercial Yoghurt Consumption on Blood Glucose Levels in Young Adults - S. Ajil , Anwar; M. Ali , Alyaa; J. Jaber , Hiba; S. Najem , Noor; F. Mzael , Noura; Marzouk, Alaa; Al-Salhi, Ahmed; Al-Shatty, Sabah (Health & Medical Sciences, 2025)
This study aimed to evaluate traditionally fermented yoghurt in comparison with selected commercially imported brands in Iraq (Kalleh, Pegah, Ramak), focusing on their chemical, microbiological, and physiological characteristics. The analyses included qualitative detection of starch and lactose, pH measurement, enumeration of lactic acid bacteria, and assessment of postprandial glycemic responses in healthy young adults over four weeks. The findings demonstrated that commercial yoghurts contained residual starch and lactose, attributable to the addition of thickening agents and the incomplete utilisation of lactose resulting from the inactivation of viable bacteria by heat treatment or irradiation. In contrast, traditional fermented yoghurt was free of such residues and exhibited significantly higher counts of active bacteria, which contributed to a notable decrease in pH during storage. From a physiological perspective, consumption of traditional yoghurt was associated with the lowest glycemic response, with peak blood glucose reaching 110 mg/dL and returning rapidly to baseline levels (95–100( mg/dL. Conversely, commercial yoghurts produced higher glycemic peaks ranging from )130 – 138( mg/dL, reflecting their higher simple sugar content and variations in processing methods. Such pronounced glycemic elevations may place additional strain on pancreatic β-cells and, if consumed regularly, could increase the risk of insulin resistance.